Implications of Social Change in the Development of Information and Communication Technology in Asian Countries - Nisa Miftachurohmah; Meisuri Meisuri; Loso Judijanto; Hayu Lusianawati (West Science Social and Humanities Studies, 2023)
This research explores the implications of social change in the development of Information and Communication Technology (ICT) within Asian countries through a comprehensive analysis of academic literature. Utilizing a bibliometric approach and thematic analysis, the study examines 980 papers published between 1922 and 2023. The thematic analysis reveals recurring terms, with "Social Change" emerging as the central focus, emphasizing the transformative impact of ICT on diverse aspects of society. Other prominent themes include "Communication," "Economic Growth," and "Social Transformation." Notably, the less occurring themes, such as "Information Society" and "Sustainable Development," signify a conceptual depth in understanding the broader societal implications of ICT. The interconnections between themes highlight the complex dynamics shaping the technological landscape in Asia. The findings provide valuable insights for researchers, policymakers, and practitioners navigating the intersection of technology and society, informing future investigations and interventions.